Study on The Cross War for Internalizing Values of Tolerance in History Learning - Jossapat Hendra Prijanto (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2017)
As we know that history is series of events that occurred which its presence must be motivated by specific causes. History does not appear immediately and stand alone without anyone arousing it. It can be said that history has a prologue and epilogue, because not all of the events that happened in the past can be recorded by history. In this topic being discussed, a crusade became the reality of the history of mankind, which had taken more or less for two hundred years. The War was the greatest conflict of two religions in the world which was between Islam that held the power at that time in part of Europe, North Africa and Asia, against the followers of Christianity who tried to seize the city of Jerusalem, which at that time ruled by Islam, the postscript is a holy city for them. Islam and Christianity are the major religions in the world that their religious teachings heavily loaded with the values of peace, tolerance and social relationships. Both in the Qur'an and Gospel, there are a lot of passages of calls for tolerance, peace and social relations. This creates a question, why the war should happen, in terms of Islam encountered in a call for dialogue with the People of the Book in a good way, as well as in Christianity which is expressed as a neighbor. Islam also considers that the Christians are a people who are closest to the Islamic ummah, and both religions actually are brothers, free from hostility and enmity.